Integrated semantic-based processes in digital home - Atanasova, Tatiana (Business Informatics, 2014)
The purpose of this work is to investigate the specifics in the development of technologies for heterogeneous data and process integration in digital home and to show possible solutions during design of integrated applications. The analysis of the integrated data can be useful for the development of improved algorithms for monitoring and control of digital networked home
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 24-33
Keywords: Process ontology; semantic; integrated data; digital home; proces ontologii; semantyka; zintegrowane dane; inteligentny dom